Digital Government Transformation in Slovenia - Rio Yusri Maulana (Universitas Padjadjaran, 2023)
The need for a shift towards digital governance is now a crucial issue in various government sectors, ICTs have become an inseparable tool considering the public's demand for more responsive, inexpensive, and inclusive government. The process of shifting, which is better known as digital transformation in Government. This article provides a comprahensive overview of how Slovenian government deliver a digital transformation strategy, as former Yugoslavian republic, Slovenia quickly achieved democratic political stability, implementing the necessary social and economic reforms to help Slovenia progressively strengthen relations in the European continent. Slovenia has made digital government a key priority in recent years through its Public Administration 2020 and Digital Slovenia 2020 strategies. Slovenia adopted key enablers from European Union (EU) to improve access and interoperability of government services. This article uses a case study to collect the necessary data and analyzing the digital transformation phenomenon and exploring the implementation of digital transformation in Slovenia. The results show that Slovenia has increasingly made digital government a key policy priority and has invested in several public policies that stress the importance of technology.